Biblical blaspheming trials of the sacred for a secular age - Sherwood, Yvonne (New York : Cambridge University Press, 2012)
"This book explores the strange persistence of 'blasphemy' in modern secular democracies by examining how accepted and prohibited ways of talking and thinking about the Bible and religion have changed over time. In a series of wide-ranging studies engaging disciplines such as politics, literature and visual theory, Yvonne Sherwood brings the Bible into dialogue with a host of interlocutors including John Locke, John Donne and the 9/11 hijackers, as well as artists such as Sarah Lucas and Rene; Magritte. Questions addressed include: [bullet] What is the origin of the common belief that the Bible, as opposed to the Qur'an, underpins liberal democratic values? [bullet] What kind of artworks does the biblical God specialise in? [bullet] If pre-modern Jewish, Christian and Islamic responses to scripture can be more 'critical' than contemporary speech about religion, how does this affect our understanding of secularity, modernity and critique?"--
Machine generated contents note: Preface; Part I. The Persistence of Blasphemy: 1. The persistence of blasphemy: the Bible as a public edifice in the secular state; Part II. Biblical Exhibitions/Biblical Exhibitionism: 2. The exquisite fruit-corpse and the surrealist works of God; 3. Prophetic scatology: prophecy and the art of sensation; Part III. Inappropriate Involvement in the Biblical Text: 4. A recently discovered letter from Isaac to Abraham (annotated); 5. Passion-binding-passion: sacrifice, masochism and the subject; Part IV. Beyond 'the Bible as Literature': 6. 'Not with a bang but a whimper': shrunken apocalypses in Ecclesiastes 12.1-8 and twentieth-century modernism; 7. The fear of loss inherent in writing: Jeremiah 36 as the tedious self-narration of a highly self-conscious scroll with Mark Brummitt; 8. John Donne and the Baroque prophets; Part V. Theo-politics, Authority and the Bible: 9. On the genesis of the alliance between the Bible and rights; 10. Binding-unbinding: pre-critical 'critique' in pre-modern Jewish, Christian and Islamic responses to the 'sacrifice' of Abraham/Ibrahim's son.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Bible -- Controversial literature; Bible -- Criticism, interpretation, etc; RELIGION / Biblical Studies / Old Testament; BIBLES / General; RELIGION / Biblical Reference / General; RELIGION / Biblical Reference / Handbooks; Electronic books